Ocean boundary making - "Johnston, Douglas M. (ed); Saunders,Philip M. (ed)" (London, 1988)
This book covers the following topics maritime boundary making in the arctic region; Ocean boundary issues in east Asia;Boundary making in the Mediterranean; The delimitation of maritime boundaries in the Caribbean; Offshore boundary delimitation in Arabian/Persian Gulf; Ocean boundaries and resource development in west Africa; Maritime boundaries and issues in southwest Pacific ocean; Ocean Boundary issues and developments in regional perspective etc.
Keywords: Territorial water Political aspects